2020
DOI: 10.5539/ijb.v12n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Ants Can Associate a Symbol with a Number of Elements Through Conditioning

Abstract: On the basis of the known numerosity abilities of the ant Myrmica sabuleti, it was checked if workers of this species could associate a symbol with a number of elements through conditioning, an ability rarely encountered in invertebrates and never mentioned in ants. Working each time on two colonies, we observed that these ants could associate a particular shape used as a symbol with 1, 2, 3 or 4 displayed dots. This acquired association was only slightly affected by a change in shape, color or size of the sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…They thus presented an anticipatory behavior relative to numerosity. The obtained ants’ conditioning scores (during the first part of the experiments) were in agreement with those commonly observed in this species, which generally equaled ca 80%, e.g., in [ 38 , 39 , 40 ]. In addition, the final scores of the experiment I (increasing sequence of numbers) were statistically equivalent to those of the experiment II (decreasing sequence of numbers).…”
Section: Discussionsupporting
confidence: 88%
“…They thus presented an anticipatory behavior relative to numerosity. The obtained ants’ conditioning scores (during the first part of the experiments) were in agreement with those commonly observed in this species, which generally equaled ca 80%, e.g., in [ 38 , 39 , 40 ]. In addition, the final scores of the experiment I (increasing sequence of numbers) were statistically equivalent to those of the experiment II (decreasing sequence of numbers).…”
Section: Discussionsupporting
confidence: 88%
“…However, bees can also acquire numerical symbolism: they can associate shapes not evoking numerosities with a given number of elements (2 or 3 elements) (Howard, Avarguès-Weber, Garcia, Greentree, & Dyer, 2019c). As for the ant M. sabuleti, we have shown that they can acquire single (Cammaerts & Cammaerts, 2020b) as well as multiple numerical symbolisms (Cammaerts & Cammaerts, 2020c).…”
Section: Introductionmentioning
confidence: 78%
“…In the course of our study on the ants' numerosity ability, we have shown among others that workers of the ant Myrmica sabuleti Meinert, 1861 can add numbers of elements when they saw them together, at once, during training (Cammaerts & Cammaerts, 2019a), and can also associate a symbol with a number of elements, at least for the numbers 1 to 4 (Cammaerts & Cammaerts, 2020b). We then wondered if these ants could add up using no longer numbers of elements presented side by side, but their corresponding symbols also presented side by side.…”
Section: Introductionmentioning
confidence: 85%
“…This is why we undertook a series of works on ants' numerical symbolism. We have previously shown that the workers of the ant M. sabuleti can learn, through conditioning, to associate a number of elements (1, 2, 3 or 4) to a corresponding symbol (Cammaerts & Cammaerts, 2020c). During this study, the ants were trained to only one number and its corresponding symbol; they thus acquired single numerical symbolism.…”
Section: Introductionmentioning
confidence: 94%